Treatment and utilization of dairy industrial waste: A review. (June 2019) - Ahmad, Talha; Aadil, Rana Muhammad; Ahmed, Haassan; Rahman, Ubaid ur; Soares, Bruna C.V.; Souza, Simone L.Q.; Pimentel, Tatiana C.; Scudino, Hugo; Guimarães, Jonas T.; Esmerino, Erick A.; Freitas, Mônica Q.; Almada, Rafael B.; et al.
Abstract: Background: Demand of dairy products is increasing in different countries, which results in the development of the dairy industry and increases in the generation of wastes. The main wastes generated are whey, dairy sludges and wastewater (processing, cleaning and sanitary). They have high nutrient concentration, biological oxygen demand (BOD), chemical oxygen demand (COD) and organic and inorganic contents. Furthermore, they can contain different sterilizing agents and a wide range of acid and alkaline detergents. Pollution due to dairy industry affects the air, soil and water quality. Scope and approach: This review aims to describe the different methods used by the dairy industry to treat wastes, highlighting their effects on quality and efficiency removal of the pollution. Especially, it focusses on biotechnological alternatives to utilize the dairy wastes. Key findings and conclusions: Physico-chemical, biological, and biotechnological methods can be used for treatment of dairy wastewaters. The physico-chemical treatment is used for reduction of milk fat and protein colloids, but it has the disadvantages of the high cost of the reagents and limited removal of COD. Biological treatments are used to remove organic material from dairy waste, however, the formation of sludge during aerobic biodegradation is a disadvantage. Aerobic and anaerobic process treatments can be used together in order to reach the effluents discharge limits for dairy wastewater. Biotechnological processes are the most recent alternatives, and can result in important products to the industries, such as whey-derived products, bioplastics, biofuels, bioenergy, organic acids, bioactive peptides, enzymes, among others. Highlights: Dairy industry generates a considerable amount of wastes. Different methods for dairy waste treatment are available. Physico-chemical methods can be used as initial step. Biotechnological methods presented better efficiency.